Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/jdv.12288
|View full text |Cite
|
Sign up to set email alerts
|

The Imbalance of Th17 cells and CD4+CD25highFoxp3+ Treg cells in patients with atopic dermatitis

Abstract: In AD, there exists an immune imbalance in Th17 and Treg cells, which may contribute to its pathogenesis and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 30 publications
5
57
1
Order By: Relevance
“…As compared with healthy controls (4.06% Tregs), significantly decreased levels of Tregs were recorded (1.6%) in eight individuals with skin sensitization to unspecified allergens, despite the fact that the average length of time since diagnosis was only 54 days. 27 Perhaps the most interesting report came from a study of melanoma patients who received an in vivo infusion of a recombinant IL-2-diphtheria toxin fusion protein, which depleted Tregs from~3% (3.5%-2%) to~2% (2.5%-1%) of CD4 + cells. Prior to depletion, only weak contact allergic responses were provoked by sensitization with the potent contact allergen diphencyprone, whereas, after depletion, very vigorous elicitation reactions to this allergen were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…As compared with healthy controls (4.06% Tregs), significantly decreased levels of Tregs were recorded (1.6%) in eight individuals with skin sensitization to unspecified allergens, despite the fact that the average length of time since diagnosis was only 54 days. 27 Perhaps the most interesting report came from a study of melanoma patients who received an in vivo infusion of a recombinant IL-2-diphtheria toxin fusion protein, which depleted Tregs from~3% (3.5%-2%) to~2% (2.5%-1%) of CD4 + cells. Prior to depletion, only weak contact allergic responses were provoked by sensitization with the potent contact allergen diphencyprone, whereas, after depletion, very vigorous elicitation reactions to this allergen were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time PCR was performed on a CFX96 Real-Time PCR system (Bio-Rad), as per the manufacturer’s instructions, using gene-specific primers for human T-bet, GATA-3, RORγt, Foxp3, and GAPDH (as internal control) (see Table I for a list of all primers). Relative gene expression was quantified by normalizing Ct values with the corresponding GAPDH value (2224). …”
Section: Methodsmentioning
confidence: 99%
“…108 Th17 cells are increased in both skin 52e54 and blood of patients with AD. 109 In a mouse model of AD deficiency of filaggrin appeared to be a driver of increased peripheral levels of Th17 cells. The authors hypothesized that this increase must be acquired as peripheral Th17 cells were found only in adult mice indicating involvement of exogenous factors.…”
Section: Il-17 and Neutrophilic Endotypementioning
confidence: 99%